Heat and mass transfer analysis of a pot-in-pot refrigerator using reynolds flow model - Pandey, Ramendra; Pesala, Bala (Journal of Thermal Science and Engineering Applications, 2016)
Heat and mass transfer analysis of evaporative cooling process in a pot-in-pot cooling system is done based on Reynolds flow hypotheses. The model proposed herein assumes that the heat transfer due to natural convection is coupled with an imaginary ambient air mass flow rate (gAo) which is an essential assumption in order to arrive at the solution for the rate of water evaporation. Effect of several parameters on the pot-in-pot system performance has been studied. The equations are iteratively solved and detailed results are presented to evaluate the cooling performance with respect to various parameters: ambient temperature, relative humidity (RH), pot height, pot radius, total heat load, thermal and hydraulic conductivity, and radiation heat transfer. It was found that pot height, pot radius, total heat load, and radiation heat transfer play a critical role in the performance of the system. The model predicts that at an ambient temperature of 50 degrees C and RH of 40%, the system achieves a maximum efficiency of 73.44% resulting in a temperature difference of nearly 20 degrees C. Similarly, for a temperature of 30 degrees C and RH of 80%, the system efficiency was minimum at 14.79%, thereby verifying the usual concept that the pot-in-pot system is best suited for hot and dry ambient conditions.